A Review on Employee Attrition Rate - Shivendra Ram Sahaya Tiwari (Journal of Advanced Research in Accounting and Finance Management, 2021)
Employee attrition is defined as the natural process by which employees leave the workforce – for example, through resignation for personal reasons or retirement – and are not immediately replaced. 'Some forms of attrition are unavoidable, like if an employee is retiring or is moving to another city. But after a certain threshold, attrition can make a big dent in your company’s bottom line as well as its culture. In this primer, we tell you all you need to know about employee attrition, and how to measure it act